Two phases of response to long-term moderate heat: Variation in thermotolerance between Arabidopsis thaliana and its relative Arabis paniculata. (February 2016) - Tang, Ting; Liu, Peile; Zheng, Guowei; Li, Weiqi
Graphical abstract: Arabis paniculata is more tolerant to long-term moderate heat than its relative Arabidopsis thaliana . Comparative lipidomic analysis indicates lipid remodelling at the early phase could favor thermotolerance of A. paniculata . Highlights: Arabis paniculata is more tolerant to long-term moderate heat than Arabidopsis . The responses of the two plants to long-term moderate heat presented two phases. The early phase displayed no significant stress symptoms. Heat shock proteins were maintained in A. paniculata at the later phase. A. paniculata synthesised lipids and reduced lipid unsaturation at the early phase. Abstract: Long-term moderate heat is often experienced by plants and will become even more common in the future due to global warming. However, the responses of plants to this stress have not been characterised. In the present study, growth between Arabidopsis thaliana and its relative Arabis paniculata upon long-term exposure to moderate heat was compared. It was found that the latter was more tolerant than the former, and the patterns of physiological and biochemical responses of both plants presented two phases. The early phase involved no significant visible morphological and physiological changes. It occurred during the first third of the heat treatment and was extended when the stress was attenuated. During the later phase, the plants died or were damaged. Heat shock proteins were dramatically induced at the early phase and gradually decreased at the later phase in A. thaliana . By contrast, the levels were induced and maintained in A. paniculata . Profiling of membrane lipids found that the two plants exhibited opposite patterns of lipid remodelling at the early phase: A. paniculata synthesised phosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine and phosphatidylinositol and showed a rapid decrease in the degree of lipid unsaturation, while A. thaliana degraded its lipids at the early phase and showed an accelerated degradation at the later phase. These biochemical adjustments during the early phase could favor the thermotolerance of A. paniculata . These results suggest that this species could thus be a model for the study of resistance to long-term moderate heat, through a strategy by which plants can adapt to long-term moderate heat.